(untitled) (Journal of Educational Management, 2012)
The studv explores the barriers which impede the progress of women faculty towards leadership positions within the public universities in Ghana. The multi-cited case study was designed to investigate the barriers that affect the progress of women faculty. One hundred and forty eight respondents from the six public universities made up the sample. Data for the study were collected using the questionnaire. The study revealed that most women faculty aspired for leadership positions within their universities. However, barriers such as role conflict, lack of publication, non existence of mentors and role models affected their progress towards leadership positions. Some of the effects of these barriers were lack of promotion, time constraints and marital strain.